Oral warty dyskeratoma: An unusual presentation - Hamid Reza Ghasemi Basir; Pedram Alirezaei; Baharereh Ebrahimi; Sina Khanali (PAGEPress Publications, 2020)
Warty dyskeratoma is an uncommon benign skin lesion, which is mostly limited to the head or neck and is rarely seen in other areas of the skin or mucous membranes. Although it is clinically similar to many skin lesions, its distinctive histopathologic features help distinguish it from other identical lesions. Herein, we report a case of warty dyskeratoma in a very unusual site (lateral border of the tongue) in a 56-year-old woman.